2022
DOI: 10.3390/antiox11050986
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Nanoparticles: The Potential Antioxidant in the Human Lung Cancer Cells

Abstract: Oxidative stress-related conditions associated with lung cells, specifically lung cancer, often lead to a poor prognosis. We hypothesized that platinum nanoparticles (PtNPs) can play a role in reversing oxidative stress in human lung adenocarcinoma A549 epithelial lung cell lines. Hydrogen peroxide (H2O2) was used to induce oxidative stress in cells, and the ability of PtNPs to lower the oxidative stress in the H2O2 treated epithelial lung cell line was determined. The differential capacity of PtNPs to remove … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Ismail et al analyzed the potential of platinum nanoparticles to decrease oxidative stress conditions in lung cancer. The data supported that epithelial lung cancer cells did not survive when they were exposed to platinum nanoparticles for 3 h [ 131 ]. Cerium oxide nanoparticles also possess anticancer properties by inducing antioxidant activity.…”
Section: Applicationssupporting
confidence: 56%
“…Ismail et al analyzed the potential of platinum nanoparticles to decrease oxidative stress conditions in lung cancer. The data supported that epithelial lung cancer cells did not survive when they were exposed to platinum nanoparticles for 3 h [ 131 ]. Cerium oxide nanoparticles also possess anticancer properties by inducing antioxidant activity.…”
Section: Applicationssupporting
confidence: 56%
“…Catalase activity according to their results was also reduced, but our research suggested increased catalase activity with time and concentration of NPs in cancer cell lines. Another study [56] examined the effect of Pt NPs on A549 cells and determined the elevation of SOD, GPx, as well as catalase activities. Their results indicate that Pt NPs might be a promising agent in the treatment of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, platinum NPs are used as drug delivery and imaging agents [ 296 , 297 , 298 , 299 ]. In vitro, analysis of platinum NPs inhibits the growth of A549 cancer cells in a dose-dependent manner [ 300 ]. Again, blood-triggered platinum NP sactas an anticancer agent by forming the protein corona [ 301 ].…”
Section: Novel Nanocarriers Based Treatment Approachmentioning
confidence: 99%
“…Again, blood-triggered platinum NP sactas an anticancer agent by forming the protein corona [ 301 ]. Another study revealed that platinum NPs reverse the oxidative stress in lung adenocarcinomas in the A549 lung cell line [ 299 , 300 ]. Again, biofabricated platinum NPs are biocompatible and have catalytic and anticancer activity [ 167 , 300 ].…”
Section: Novel Nanocarriers Based Treatment Approachmentioning
confidence: 99%